2022
DOI: 10.57178/atestasi.v5i1.360
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Good Corporate Governance on Financial Performance Through Corporate Social Responsibility

Abstract: This study examines and determines the effect of good corporate governance on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange through Corporate Social Responsibility. This research is quantitative research with a descriptive statistical approach. The population in this study are manufacturing companies in the food and beverage sub-sector and 28 companies listed on the Indonesia Stock Exchange for the 2019-2021 period. Determined the sample using purposive sampling an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
(13 reference statements)
0
1
0
2
Order By: Relevance
“…Namun, seringkali praktik di lapangan tidak sepenuhnya mencerminkan prinsip-prinsip pengelolaan keuangan yang baik (Choerunisa, 2018). Kasus penyelewengan dana, inefisiensi pengelolaan, dan kurangnya transparansi masih sering terjadi (Indriasi, et al, 2019;Indriakati & Daga, 2022). Hal ini menimbulkan pertanyaan tentang seberapa efektif implementasi good governance dan sistem pengendalian internal dalam konteks pengelolaan keuangan di institusi pendidikan (Kewo & Tanor, 2020).…”
Section: Pendahuluanunclassified
“…Namun, seringkali praktik di lapangan tidak sepenuhnya mencerminkan prinsip-prinsip pengelolaan keuangan yang baik (Choerunisa, 2018). Kasus penyelewengan dana, inefisiensi pengelolaan, dan kurangnya transparansi masih sering terjadi (Indriasi, et al, 2019;Indriakati & Daga, 2022). Hal ini menimbulkan pertanyaan tentang seberapa efektif implementasi good governance dan sistem pengendalian internal dalam konteks pengelolaan keuangan di institusi pendidikan (Kewo & Tanor, 2020).…”
Section: Pendahuluanunclassified
“…Untuk itu, aparatur Negara diharapkan melaksanakan tugas dan tanggung jawabnya secara efektif dan efisien. Diharapkan dengan penerapan good governance dapat mengembalikan dan membangun kembali kepercayaan masyarakat terhadap pemerintah (Indriakati & Daga, 2022).…”
Section: Pendahuluanunclassified
“…Jorgie Jovancha Appy (2021) in the paper titled "The Influence of Good Corporate Governance, Corporate Social Responsibility, and Environmental Performance on Corporate Financial Performance" indicated that the financial performance of companies is not own positively affected corporate social responsibility [4]. In the research conducted by Time [5], the examination of social performance indicators showed no notewor influence financial performance., as social actions within a company affect reputation differently from financial performance.…”
Section: Introductionmentioning
confidence: 99%